Binding number condition for fractional (<> />n’> m)-critical deleted graph in the new Setting - Wu, Jianzhang; Gao, Wei (Utilitas Mathematica, 2018)
In Gao and Wang [3], it is proved that G is a fractional ([removed] In this paper, we obtain a new binding number condition for fractional (g/n',m)- critical deleted graph in the setting that there is a gap r between f(x) and for each x G V'(G). It is presented that G is a fractional (g,ftn)' critical deleted graph if bind(G) >-im which extends the previous conclusion manifested by Gao and Wang [3]. Finally, we give an example to show that our result is best possible in some sense. © 2018 Utilitas Mathematica Publishing Incorporated. All rights reserved.